The Expert System Determines Children's Emotions with Learning Achievement Using The Web-based Damster Shafer Method - Nasution, Cellina Roanda (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
Psychology studies human behavior and mental processes is possible there involved the use of technology, but the use and utilization of technology in the field of psychology is felt still lacking. One method that is still widely used in psychology that is by making the Demster Shafer sheet. Demster Shafer method can be modified in the form of computer applications, where the application is using the knowledge of experts of psychology entered into the computer called expert systems applications. Application of expert system is designed to determine the child's learning style at primary school age. Application of expert systems is expected to overcome the problems of determining the child's learning style. In addition, it can be used as a support in the field of psychology and can be used for public purposes and individuals in general.